Płaca minimalna jako narzędzie polityki ekonomicznej - Polańska, Aurelia (Wydział Prawa i Administracji UAM, 1988)
In the Polish People's Republic the minimum pay has always been and still is a means of a central pay policy, used to set back the growth of pay of people employed in the socialized sector. Its value has always been and still is lowered, for it does not guarantee the satisfaction of basic needs of an employee and his/ /her dependents. Such an approach brought about only negative effects in the sphere of motivation to work. In 1994 there will be a 100th anniversary of introducing the minimum pay in New Zealand. On that occasion a comparison between purchasing power of minimum pays in various countries will be conducted. May Poland not take a discrediting place! The minimum pay, just like any other pay, must perform income and motivating functions. One may expect the economic revival to come when people are able to live on one pay, also on the minimum pay. It would increase the value of work. The theses of the 2nd stage of the economic reform did not raise this issue; it is one of the reasons for this article to have been written.
The minimum pay as a means of economic policy